A sensorimotor area in the songbird brain is required for production of vocalizations in the song learning period of development. Issue 11 (4th March 2016) - Piristine, Hande C.; Choetso, Tenzin; Gobes, Sharon M. H.
ABSTRACT: Sensory feedback is essential for acquiring and maintaining complex motor behaviors, including birdsong. In zebra finches, auditory feedback reaches the song control circuits primarily through the nucleus interfacialis nidopalii (Nif), which provides excitatory input to HVC (proper name)—a premotor region essential for the production of learned vocalizations. Despite being one of the major inputs to the song control pathway, the role of Nif in generating vocalizations is not well understood. To address this, we transiently inactivated Nif in late juvenile zebra finches. Upon Nif inactivation (in both hemispheres or on one side only), birds went from singing stereotyped zebra finch song to uttering highly variable and unstructured vocalizations resembling sub‐song, an early juvenile song form driven by a basal ganglia circuit. Simultaneously inactivating Nif and LMAN (lateral magnocellular nucleus of the anterior nidopallium), the output nucleus of a basal ganglia circuit, inhibited song production altogether. These results suggest that Nif is required for generating the premotor drive for song. Permanent Nif lesions, in contrast, have only transient effects on vocal production, with song recovering within a day. The sensorimotor nucleus Nif thus produces a premotor drive to the motor pathway that is acutely required for generating learned vocalizations, but once permanently removed, the song system can compensate for its absence. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 76: 1213–1225, 2016